Comprehensive mapping of the bull sperm surface proteome - Byrne, Keren; Leahy, Tamara; McCulloch, Russell; Colgrave, Michelle L.; Holland, Michael K. (Proteomics (Weinheim), 2012)
While the mechanisms that underpin maturation, capacitation, and sperm–egg interactions remain elusive it is known that these essential fertilisation events are driven by the protein complement of the sperm surface. Understanding these processes is critical to the regulation of animal reproduction, but few studies have attempted to define the full repertoire of sperm surface proteins in animals of agricultural importance. Recent developments in proteomics technologies, subcellular fractionation, and optimised solubilisation strategies have enhanced the potential for the comprehensive characterisation of the sperm surface proteome. Here we report the identification of 419 proteins from a mature bull sperm plasma membrane fraction. Protein domain enrichment analyses indicate that 67% of all the proteins identified may be membrane associated. A large number of the proteins identified are conserved between mammalian species and are reported to play key roles in sperm–egg communication, capacitation and fertility. The major functional pathways identified were related to protein catabolism (26S proteasome complex), chaperonin‐containing TCP‐1 (CCT) complex and fundamental metabolic processes such as glycolysis and energy production. We have also identified 118 predicted transmembrane proteins, some of which are implicated in cell adhesion, acrosomal exocytosis, vesicle transport and immunity and fertilisation events, while others have not been reported in mammalian LC‐MS‐derived sperm proteomes to date. Comparative proteomics and functional network analyses of these proteins expand our system's level of understanding of the bull sperm proteome and provide important clues toward finding the essential conserved function of these proteins.